"It's like they don't see us at all": A Critical Race Theory critique of dual language bilingual education for Black children. (March 2022) - Frieson, Brittany L.
Abstract: This article highlights the institutional harm that many dual language bilingual education (DLBE) programs can impose upon Black American children. By uncovering the ways that bilingual education is often complicit in educational injustice for Black children, this article argues for a closer interrogation of unquestioned DLBE policies and practices through an analysis that gives centrality to race and intersectionality. In this piece, a composite counterstory is crafted using African American Language to powerfully facilitate a Critical Race Theory-informed critique of DLBE's institutional structures and practices that detail the experiences of many Black children in DLBE programs. A recommendation for intersectional approaches to DLBE that center, support, and advocate for intersectional consciousness across all Black identities is offered.